2022
DOI: 10.1152/japplphysiol.00757.2021
|View full text |Cite
|
Sign up to set email alerts
|

Acid-base balance at high altitude in lowlanders and indigenous highlanders

Abstract: High-altitude exposure results in a hyperventilatory-induced respiratory alkalosis followed by renal compensation (bicarbonaturia) to return arterial blood pH(a) toward sea-level values. However, acid-base balance has not been comprehensively examined in both lowlanders and indigenous populations - where the latter are thought to be fully adapted to high-altitude. The purpose of this investigation was to compare acid-base balance between acclimatizing lowlanders, and Andean and Sherpa highlanders at various al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
0
8
0
1
Order By: Relevance
“…Second, we would like to acknowledge that there are physiological differences in the adaptative response to short versus long stays at HA, which have been well summarized elsewhere (Moore, 2017; Peacock, 1998). The current investigation took place after 21–28 days at HA, with blood work confirming the expansion of haemoglobin/haematocrit, and stabilization of PaO2${P}_{{\rm{aO}}_{\rm{2}}}$, PaCO2${P}_{{\rm{aCO}}_{\rm{2}}}$, HCO 3 − (Tymko et al., 2022), and the expected persistent increase in muscle sympathetic nervous system activity (Tymko, Lawley et al., 2020). Third, we would like to acknowledge the relatively small sample size used during this investigation.…”
Section: Discussionmentioning
confidence: 76%
“…Second, we would like to acknowledge that there are physiological differences in the adaptative response to short versus long stays at HA, which have been well summarized elsewhere (Moore, 2017; Peacock, 1998). The current investigation took place after 21–28 days at HA, with blood work confirming the expansion of haemoglobin/haematocrit, and stabilization of PaO2${P}_{{\rm{aO}}_{\rm{2}}}$, PaCO2${P}_{{\rm{aCO}}_{\rm{2}}}$, HCO 3 − (Tymko et al., 2022), and the expected persistent increase in muscle sympathetic nervous system activity (Tymko, Lawley et al., 2020). Third, we would like to acknowledge the relatively small sample size used during this investigation.…”
Section: Discussionmentioning
confidence: 76%
“…For the Tymko et al. (2022) study the arterial state changes alone would reduce tissue O 2 /CO 2 to 52% of baseline, essentially at the critical level.…”
Section: Resultsmentioning
confidence: 97%
“…When a healthy subject living near sea level travels to high altitude and remains they exhibit a range of physiological changes as they acclimatize to the lower atmospheric P O2$_{\text{O}_{2}}$. Table 3 lists the measured changes in the physiological state for three studies of Lowlanders partially acclimatized to an elevation of ∼5000 m. The columns from left to right are arranged in decreasing order of the length of stay at altitude: 3 weeks at an altitude of 5260 m (Moller et al., 2002); 14–20 days at 5050 m (Caldwell et al., 2021); and 14 days at 5050 m (Tymko et al., 2022). In the first study (column 1) CBF and CMRO 2 also were measured and found to be unchanged from sea level.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations